Bank Ownership, Firm Value and Firm Capital Structure in Europe - Lieven Baert; Rudi Vander Vennet (Deutsches Institut für Wirtschaftsforschung (DIW), 2009)
We investigate whether or not banks play a positive role in the ownership structure of European listed firms. We distinguish between banks and other institutional investors as shareholders and examine empirically the relationship between financial institution ownership and the performance of the firms in which they hold equity. Our main finding is that after controlling for the capital structure decision of the firms and the ownership decision of financial institutions in a simultaneous equations model, we find that there is a negative relationship between financial institution ownership and the market value of firms, measured as the Tobin's Q. This is in contradiction with the monitoring hypothesis.
info:eu-repo/grantAgreement/EC/FP7/217266
Keywords: G32; G20; 330; Financial institution ownership; Firm value; Capital structure